2019
DOI: 10.1521/jscp.2019.38.6.451
|View full text |Cite
|
Sign up to set email alerts
|

Emotions as Context: Do the Naturalistic Effects of Emotion Regulation Strategies Depend on the Regulated Emotion?

Abstract: Researchers have examined how several contexts impact the effectiveness of emotion regulation strategies. However, few have considered the emotion-to-be-regulated as a context of interest. Specific emotions are important contexts because they may require particular responses to internal and external stimuli for optimal regulation. Ninety-two undergraduates completed 10 days of ecological momentary assessment, reporting their current mood, recent emotions, and emotion regulation strategies three times per day. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 30 publications
7
28
0
1
Order By: Relevance
“…When discrete emotional responses were assessed, participants in the current study most frequently reported experiences of anxiety and joy. These results were consistent with a sample of American undergraduate students oversampled to be elevated in neuroticism (Heiy & Cheavens, 2014;Southward et al, 2019). However, these results differed somewhat from a German sample of people with BPD (Kockler et al, 2019) in which participants reported experiencing anger most frequently, followed closely by sadness and anxiety.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…When discrete emotional responses were assessed, participants in the current study most frequently reported experiences of anxiety and joy. These results were consistent with a sample of American undergraduate students oversampled to be elevated in neuroticism (Heiy & Cheavens, 2014;Southward et al, 2019). However, these results differed somewhat from a German sample of people with BPD (Kockler et al, 2019) in which participants reported experiencing anger most frequently, followed closely by sadness and anxiety.…”
Section: Discussionsupporting
confidence: 82%
“…Alternatively, acceptance may be an underdeveloped skill for people with BPD (Southward & Cheavens, 2020), who may have instead practiced resignation or rumination instead of nonjudgmental, present-moment acceptance. In contrast, undergraduate students oversampled for neuroticism reported that acceptance was associated with better and improving moods, whereas emotional suppression, which is conceptually similar to pushing emotions away, was unrelated to changes in mood (Heiy & Cheavens, 2014;Southward et al, 2019). Together, these results may suggest that acceptance is perceived as more effective in the moment if it can be used in response to more positively-valenced emotions, whereas suppression is viewed as more effective if it can be used in response to more negatively-valenced emotions.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, acceptance is quite distinct from other frequently studied ways of regulating emotion (e.g., suppression, most forms of cognitive reappraisal, rumination) that are most often based on some form of active modification of emotional state in terms of quality, strength, length, or frequency of emotion (Gross, 2015). Despite these differences, acceptance is present in psychological research on emotion regulation and is often compared with other regulatory strategies (e.g., Liverant et al, 2008;Aldao et al, 2010;Naragon-Gainey et al, 2017;Southward et al, 2019). However, despite the presence of acceptance in the work of both psychological practitioners and theoreticians, we stumble upon significant difficulties when trying to find acceptance in broader theoretical models of emotion regulation.…”
mentioning
confidence: 99%
“…It seems that the discussed methodological differences can have significant importance for the outcomes of the research, as they lead to differential consequences on the cognitive (e.g., the level of comprehension and memorization of instruction) as well as motivational level (e.g., willingness to apply the instruction)-however, in most research, these factors are not controlled. Additionally, recent research showed that effectiveness of emotion regulation strategies can be dependent on the specific emotion that is targeted in the regulation episode, which should be further explored in future studies (Southward et al, 2019). Also, it appears that, under particular circumstances, the use of acceptance can be greater among older adults (Allen and Windsor, 2019), so the age of participants should be systematically examined in research.…”
mentioning
confidence: 99%
“…when used in response to a stimulus, momentary experiential avoidance1 has been associated with greater negative affect (Heiy & Cheavens, 2014;Southward, Heiy, & Cheavens, 2019). In contrast, momentary expressive suppression has been associated with lower negative affect (Webb, Miles, & Sheeran, 2012).…”
Section: Momentary Use Of Experiential Avoidance and Expressive Supprmentioning
confidence: 99%